PENGARUH PERENDAMAN EKSTRAK DAUN CEREMAI (Phyllanthus acidus [L] skeels) TERHADAP TOTAL ERITROSIT DAN KELULUSHIDUPAN IKAN MAS (Cyprinus carpio) YANG DIINFEKSI BAKTERI Aeromonas hydrophila - Setyani, Rina; Sarjito, - -; Haditomo, Alfabetian Harjuno Condro (Journal of Aquaculture Management and Technology, 2018)
Ikan mas (Cyprinus carpio) merupakan jenis ikan konsumsi air tawar yang banyak dibudidayakan. Salah satu kendala dalam budidaya ikan mas adalah serangan penyakit Motile Aeromonas Septicemia (MAS), penyakit yang disebabkan oleh bakteri Aeromonas hydrophila. Daun ceremai dapat digunakan sebagai bahan alternatif untuk pengobatan sebagai antibakteri. Penelitian ini bertujuan untuk mengetahui pengaruh perendaman dan dosis terbaik ekstrak daun ceremai terhadap total eritrosit serta kelulushidupan ikan mas yang diinfeksi bakteri Aeromonas hydrophila. Perlakuan dalam penelitian ini berupa perendaman ekstrak daun ceremai dengan 4 dosis berbeda dan 3 kali ulangan yaitu perlakuan A (0 ppm), perlakuan B (1000 ppm), perlakuan C (2000 ppm) dan perlakuan D (3000 ppm). Ikan mas di injeksi bakteri A. hydrophila sebanyak 0,1 mL dengan konsentrasi 107 CFU/mL secara intramuskular. Setelah menunjukkan gejala klinis berupa warna tubuh memudar, peradangan yang kemudian menjadi luka (ulcer) di bekas suntikan dan bintik-bintik merah pada permukaan tubuh, ikan mas direndam dalam ekstrak daun ceremai selama 20 menit. Hasil pengamatan diperoleh total eritrosit hari ke-1 pasca iinfeksi mengalami penurunan disemua perlakuan setelah dilakukan perendaman pada hari ke-7 dan hari ke-13 total eritrosit mengalami kenaikan kecuali pada perlakuan A. Nilai kelulushidupan tertinggi terdapat pada perlakuan B sebesar 63,33% diikuti oleh perlakuan C sebesar 33,33%, perlakuan D sebesar 20,00% dan pada perlakuan A sebesar 0%. Penggunaan ekstrak daun ceremai terbukti berpengaruh nyata terhadap total eritrosit dan kelulushidupan (P<0,05) ikan mas yang diinfeksi bakteri A. hydrophila. Hasil penelitian menunjukkan bahwa dosis ekstrak duan ceremai 1000 ppm dapat menyembuhkan ikan mas yang diinfeksi bakteri A. hydrophila.Carp (Cyprinus carpio) is a type of freshwater fish consumption that is widely cultivated. One of the obstacles in the cultivation of carp is the attack of Motile Aeromonas Septicemia (MAS), a disease caused by aeromonas hydrophila bacteria. Ceremai of leaves can be used as an alternative ingredient for treatment as antibacterial. The purpose of this study is to determine the effect of immersion and the best dose of ceremai leaf extract againts total erythrocytes and survival rate of a carp infected by A. hydrophila. The treatment in this research were soaking of ceremai leaf extract with 4 different dosage and 3 replicates is treatments were A (0 ppm), B (1000 ppm), C (2000 ppm) and D (3000 ppm). Carp in injection of A. hydrophila bacteria as much as 0,1mL with concentration 107CFU/mLintramuscularly. After showingthe clinicalsymptomsof body color fades, inflammation that become wound (ulcer) at the injection site and red spots on the surface of the body, carp is immersion in the leaf extract of the ceremaifor 20 minutes. The observasion showed thatthe total erytrocytes at1st days decrease in all treatment after immersion thatthe total erytrocytes at 7th days and 13th days increase except in treatment A.The highestsurvival valuewas in treatment B of 63,33% followed by treatment C 33,33%, treatment D of 20,00%andat treatment A of 0%. The use of ceremai leaf extract proved significantly effect on the total erythrocyte and survival rate (P<0,05) a carp infected by A. Hydrophila. The results showed that dosage 1000 ppm ceremai leaf extract can cure carp infected by A. hydrophila. Carp (Cyprinus carpio) is a type of freshwater fish consumption that is widely cultivated. One of the obstacles in the cultivation of carp is the attack of Motile Aeromonas Septicemia (MAS), a disease caused by aeromonas hydrophila bacteria. Ceremai of leaves can be used as an alternative ingredient for treatment as antibacterial. The purpose of this study is to determine the effect of immersion and the best dose of ceremai leaf extract againts total erythrocytes and survival rate of a carp infected by A. hydrophila. The treatment in this research were soaking of ceremai leaf extract with 4 different dosage and 3 replicates is treatments were A (0 ppm), B (1000 ppm), C (2000 ppm) and D (3000 ppm). Carp in injection of A. hydrophila bacteria as much as 0,1mL with concentration 107CFU/mLintramuscularly. After showingthe clinicalsymptomsof body color fades, inflammation that become wound (ulcer) at the injection site and red spots on the surface of the body, carp is immersion in the leaf extract of the ceremaifor 20 minutes. The observasion showed thatthe total erytrocytes at1st days decrease in all treatment after immersion thatthe total erytrocytes at 7th days and 13th days increase except in treatment A.The highestsurvival valuewas in treatment B of 63,33% followed by treatment C 33,33%, treatment D of 20,00%andat treatment A of 0%. The use of ceremai leaf extract proved significantly effect on the total erythrocyte and survival rate (P<0,05) a carp infected by A. Hydrophila. The results showed that dosage 1000 ppm ceremai leaf extract can cure carp infected by A. hydrophila.